Efektivitas Model Situation-Based Learning (SBL) Berbantuan Ispring Suite Terhadap Kemampuan Pemahaman Konsep Matematis - Julaeha, Laela; Heriyana, Tio (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study is to compare the effectiveness of using the SBL model assisted by iSpring Suite with the conventional model. A quantitative approach with Nonequivalent Pretest-Posttest Only Control Group Designs was used. The research sample consisted of class 8A as the experimental class and class 8B as the control class, which were selected using purposive sampling techniques. Questions and questionnaires were used as instruments. Statistical data analysis was applied, including prerequisite tests, Mann-Whitney U tests, Z-approach tests, independent two-sample t-tests, and questionnaire processing using a Likert scale. The results of the study show: (1) There was a difference in the average and an increase in mathematical concept comprehension ability. (2) The students' responses to the questionnaire strongly agreed that the SBL learning model assisted by iSpring Suite should be implemented to improve mathematical concept comprehension ability